Advanced Green composites using liquid crystalline cellulose fibers and waxy maize starch based resin. (7th July 2018) - Rahman, Muhammad M.; Netravali, Anil N.
Abstract: Advanced green composites have been fabricated by using modified liquid crystalline cellulose (M-LCC) fibers and micro-fibrillated cellulose (MFC) modified waxy maize starch (M-WMS) based resin. LCC fibers, as a reinforcement, were modified in terms of tensile properties by a combination of chemical and heat treatment, under a predetermined tension. The surface topography, crystallinity, molecular alignment, and mechanical properties of M-LCC fibers were investigated to determine the effects of combination modification process on the fibers. M-WMS, as a resin, was prepared by two steps. In the first step, an environment-friendly cross-linker, 1, 2, 3, 4-butane tetracarboxylic acid (BTCA), was used to improve the water resistance and tensile properties of the resin. In the second step, 'MFC', as reinforcing agent, was dispersed in the cross-linked resin to obtain substantial improvements in its tensile properties. Unidirectional advanced green composites consisting of M-LCC fibers and M-WMS were fabricated using hand lay-up followed by a compression molding process. The results showed that the M-LCC fibers had strength close to 2 GPa and the composites had strength close to 800 MPa. These advanced green composites could be used in structural applications.